Uric acid lowering therapy for prevention of cardiovascular disease requires further evidence to be validated - Oda, Eiji (Journal of Laboratory and Precision Medicine, 2017)
It has been observed since the late 19th century that gout is associated with hypertension, diabetes, kidney disease and cardiovascular disease (1). In 1897, Dr. Davis suggested that hypertension in gout might partly be due to hyperuricemia which increases arteriolar tonus (1).